PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA LEAFLET TERHADAP PENGETAHUAN WUS DALAM PEMERIKSAAN PAYUDARA SENDIRI (SADARI) DI DESA KEMBANG JATIPURNO WONOGIRI - Sulistiani, Ardiani; Zulaika, Artanti (Jurnal Komunikasi Kesehatan, 2018)
The aim of this study was to determine the effect of health education using leaflet media on WUS' knowledge of breast self-examination (BSE). This research was conducted using the Quasi Experimental method with the One Group Pre Post Test Design approach. Sampling was taken using the sample Quota Sampling technique with inclusion criteria to obtain a sample of 30 WUS in Kembang Village, Jatipurno Wonogiri subdistrict. Based on the results of the Paired Sample T Test, it can be seen that the significance value or p-value is 0.000 < 0.05, so it can be concluded that there is an influence of education through leaflets on the knowledge of women of childbearing age about breast self-examination in Kembang village, Jatipurno Wonogiri subdistrict. It is hoped that there will be activities that can increase knowledge about breast self-examination in Kembang village, Jatipurno Wonogiri subdistrict so that WUS’can practice it in daily life as an effort to detect breast cancer early.